2016
DOI: 10.1016/j.jnucmat.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the effect of surface electric field in the growth of tungsten nano-tendril morphology due to low energy helium irradiation

Abstract: The mechanisms responsible for and controlling the growth of tungsten nano-tendrils (or "fuzz") under low-energy helium plasma exposure remain unclear. For the first time in nanotendril experiments, the plasma sheath-produced electric field and the helium (He) ion energy have been decoupled, showing that the sheath electric field has little impact on nano-tendril growth, eliminating a possible cause for tendril growth. The well-established necessary growth conditions for W fuzz were maintained with He ion flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Finally, the possibility that electrostatic effects (Karpov 2014) may contribute to fuzz growth was been recently explored in two separate investigations (Fiflis et al 2016, Woller et al 2016. No evidence for such a mechanism was found in either work at the electric field magnitudes typically generated in plasma sheaths.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…Finally, the possibility that electrostatic effects (Karpov 2014) may contribute to fuzz growth was been recently explored in two separate investigations (Fiflis et al 2016, Woller et al 2016. No evidence for such a mechanism was found in either work at the electric field magnitudes typically generated in plasma sheaths.…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…In fact, many transient events due to plasma instability such as ELMs and disruptions can create enough stresses and thermal loads to break or easily remove the W fuzz [17]. Therefore, contamination of plasma due to the presence of fuzzy W surfaces is always a serious concern [8,13,18]. Additionally, the presence of W fuzz on a W surface may alter and significantly degrade the W thermal properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…To the date, researchers have concluded that the major factors significantly influence the W fuzz growth are surface temperature, incident He ion-energy, -flux, and -fluence [18]. The lower energy threshold for fuzz growth is 12 to 30 eV [2,19,20] depending up on sample grade, plasma conditions, and surface temperature used during the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with the electric field from the plasma present could accelerate this. However, two studies have shown that electric field variation has no effect on fuzz growth [30,31], so this mechanism has been rejected.…”
Section: Electrostatic Growthmentioning
confidence: 99%